2008
DOI: 10.1038/ismej.2008.93
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of homologous recombination rates in bacteria and archaea

Abstract: It is a standard practice to test for the signature of homologous recombination in studies examining the genetic diversity of bacterial populations. Although it has emerged that homologous recombination rates can vary widely between species, comparing the results from different studies is made difficult by the diversity of estimation methods used. Here, Multi Locus Sequence Typing (MLST) datasets from a wide variety of bacteria and archaea are analyzed using the ClonalFrame method. This enables a direct compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
529
14
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(613 citation statements)
references
References 87 publications
(61 reference statements)
62
529
14
1
Order By: Relevance
“…Considering the entire R. solanacearum population, the standardized index of association, I a s (Maynard Smith et al, 1993;Haubold et al, 1998), was significantly different from 0, indicating a high level of linkage disequilibrium and a clonal genetic structure (Table 4). R. solanacearum as a whole had an intermediate relative effect of recombination and mutation (r/m ¼ 1.6), confirming previous results (Vos and Didelot, 2008). However, when calculated on the different phylotypes, I a s indicated that phylotype I population was in linkage equilibrium Gene exchanges are represented with arrows and orientated from the donor (minor parent) to the recombinant.…”
Section: Recombination and Mutation Among Phylotypessupporting
confidence: 73%
See 2 more Smart Citations
“…Considering the entire R. solanacearum population, the standardized index of association, I a s (Maynard Smith et al, 1993;Haubold et al, 1998), was significantly different from 0, indicating a high level of linkage disequilibrium and a clonal genetic structure (Table 4). R. solanacearum as a whole had an intermediate relative effect of recombination and mutation (r/m ¼ 1.6), confirming previous results (Vos and Didelot, 2008). However, when calculated on the different phylotypes, I a s indicated that phylotype I population was in linkage equilibrium Gene exchanges are represented with arrows and orientated from the donor (minor parent) to the recombinant.…”
Section: Recombination and Mutation Among Phylotypessupporting
confidence: 73%
“…Among the recombination processes, the evolutionary importance of horizontal gene transfer has been highlighted by the tremendously increasing number of whole-genome sequences available (Martin and Beiko, 2010), and has mainly been studied on animal or human pathogenic bacteria (Achtman, 2008;Didelot and Maiden, 2010). Although some recent studies address this question on Pseudomonas syringae (Yan et al, 2008) or Xanthomonas campestris (Fargier et al, 2011), data are far less numerous on plant-associated bacteria, and more specifically plant pathogenic bacteria (Vos and Didelot, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we attributed this to the SAGs being incomplete and fragmented, because when the SAGs were compared with other SAR11 genomes, syntenic genes were a characteristically high percentage of the total shared genes. High amounts of local synteny may seem unlikely given predicted SAR11 recombination rates are among the highest measured for prokaryotes (Vergin et al, 2007;Vos and Didelot, 2009), however, it was shown previously that much of the rearrangement within genomes occurs at operon boundaries, and thus local synteny is not disrupted . Further, the rates in Vergin et al (2007) were restricted to closely related organisms within subclade Ia.…”
Section: Subclade Ic Relative Abundance In Metagenomic Datasetsmentioning
confidence: 99%
“…The rate of homologous recombination (r) in C. difficile is estimated to be relatively low, and is estimated to have effect ~4 times lower than point mutation (m), (r/m=0.25) (Dingle et al, 2011;Vos and Didelot, 2009). This rate could be an underestimation, however, if barriers between lineages existed, such as geographical separation.…”
Section: Accepted Manuscript 13mentioning
confidence: 99%